Analisis Korelasi Antara Keterampilan Komunikasi Guru Dan Motivasi Belajar Siswa Sekolah Dasar - Iza Faridatul Amalia; Rodia Tammardiah Hasibuan; Daman Daman; Asmaul Husna; Sasmiyarti Sasmiyarti; Rahmatul Hayati (Departement of Mathematics Education, 2024)
Teachers and students have a communication role in education. Communication techniques in learning are how to convey messages or learning materials and how to develop dialogue between teachers and students or fellow students effectively. In the process of communication, teachers can convey what they have to their students with the aim that the knowledge and experience that a teacher has can also be owned by his students. Teachers' communication skills greatly affect students' learning motivation. Student learning motivation is the encouragement in students to take an action in order to master new abilities in the form of knowledge, skills, abilities, willingness, habits and attitudes. If students understand the learning objectives, they are likely to be motivated to learn which can be measured by aspects of student learning motivation.